Greenhouse gas emissions from cattle production sector in South Korea - Andi Febrisiantosa; J.H. Lee; H.L. Choi (Jurnal Ilmu Ternak dan Veteriner, 2016)
South Korea has declared to reduce greenhouse gas emissions by 30% compared to the current level by the year 2020. The greenhouse gas emissions from the cattle production sector in South Korea were evaluated in this study. The greenhouse gas emissions of dairy cattle, Non-Korean native cattle, and Korean native (Hanwoo) cattle production activities in 16 local administrative provinces of South Korea over a ten-year period (2005–2014) were estimated using the methodology specified by the Guidelines for National Greenhouse Gas Inventory of the IPCC (2006). The emissions studied herein included methane from enteric fermentation, methane from manure management, nitrous oxide from manure management and carbon dioxide from direct on-farm energy use. Over the last ten years, Hanwoo cattle production activities were the primary contributor of CH4 from enteric fermentation, CH4 from manure management, NO2 from manure management and CO2 from on-farm energy use in the cattle livestock sector of South Korea, which comprised to 83.52% of total emissions from cattle production sector.